A novel propane pre-cooled mixed refrigerant process for coproduction of LNG and high purity ethane. (1st July 2020) - He, Ting; Lin, Wensheng
Abstract: For high ethane-containing natural gas, such as shale gas, separation and purification of ethane during liquefaction can improve economic benefits. A novel process of propane pre-cooled mixed refrigerant natural gas liquefaction integrated with cryogenic distillation for ethane separation is introduced and analyzed, which produce both liquefied natural gas (LNG) and liquefied ethane at the same time. The chemical engineering software HYSYS is used to simulate the process, and the liquefaction operation parameters of the system are optimized by genetic algorithm to reduce energy consumption. The results show that the proposed process can effectively achieve ethane separation, with the purity of ethane product over 99.5% and ethane recovery rate higher than 99.5%. As the ethane content in the feed gas increases, the specific power consumption and exergy efficiency of the system decrease slightly. When ethane content is in the range of 10%–40%, the optimized specific energy consumption is around 0.44 kWh/Nm 3 (natural gas), and the exergy efficiency is around 47%. Highlights: C3MR natural gas liquefaction process integrated with ethane separation are proposed. LNG and liquid ethane are both produced, with fairly low specific power consumption. Self-supply of the distillation column heat load is achieved by heat integration. The purity and recovery rate of liquid ethane products are both higher than 99.5%. The specific power consumption decreases slightly with ethane content increasing.